Nursing as a career - Chandler, Caroline A. (Caroline Augusta) 1906- (Dodd, Mead, 1970)
Describes nursing as a profession, including the possible preparatory tryouts as a volunteer, a candy striper, a nurse's aide, and other training leading to qualification as an R.N.